Adhesive capsulitis: How to treat your patient? - Dubljanin Raspopovic, Emilija; Nedeljkovic, Una; Tomanovic Vujadinovic, Sanja; Grajic, Mirko; Krstic, Nevena; Konstantinovic, Ljubica (Vojnosanitetski pregled, 2013)
Key words: bursitis; shoulder joint; diagnosis; drug therapy; physical therapy modalities; rehabilitation; treatment outcome.